2023
DOI: 10.3390/children10050830
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Perioperative Aspects Favor the Use of Percutaneous Crossed Pinning over Antegrade Nailing in Pediatric Supracondylar Fractures—A Retrospective Comparative Study

Abstract: (1) Background: Displaced supracondylar humeral fractures in pediatric patients can be treated by either antegrade nailing (AN) or percutaneous crossed pinning (PCP). The aim of this study was to compare the intra- and perioperative management, complications and outcome of AN and PCP. (2) Methods: This retrospective study enrolled 271 individuals (median age 5 years, IQR 4–7 years) who underwent AN (n = 173) or PCP (n = 98). Patient history was analyzed for incidence of nerve injuries, postoperative treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, Liu et al showed superior mechanical stability for CRK compared to ESIN or external fixation [40]. Greve et al also showed slightly superior results for CRK compared to ESIN regarding intraoperative fluoroscopy time and duration of surgery, although the nature of the study was retrospective and a cast was routinely applied also in the ESIN group [41]. We shifted from ESIN's to K-wires because of our impression that we had better postoperative reduction with K-wires.…”
Section: Discussionmentioning
confidence: 94%
“…However, Liu et al showed superior mechanical stability for CRK compared to ESIN or external fixation [40]. Greve et al also showed slightly superior results for CRK compared to ESIN regarding intraoperative fluoroscopy time and duration of surgery, although the nature of the study was retrospective and a cast was routinely applied also in the ESIN group [41]. We shifted from ESIN's to K-wires because of our impression that we had better postoperative reduction with K-wires.…”
Section: Discussionmentioning
confidence: 94%